THE EFFECT OF RELIGIOUSNESS, ACCESS TO CAPITAL, AND ENTREPRENEURIAL KNOWLEDGE ON THE FINANCIAL PERFORMANCE OF STREET VENDORS AT THE AL-ALAM MOSQUE IN TELUK KENDARI - Suman Anselah; Marzuki; Hamka (Referensi Islamika: Jurnal Studi Islam, 2025)
This study aims to analyze the effect of religiosity, access to capital, and entrepreneurial knowledge on the financial performance of street vendors at the Al-Alam Mosque, Teluk Kendari. This study adopts a quantitative approach using a census method involving 75 street vendors. Data were collected through questionnaires and analyzed using descriptive statistics and multiple linear regression. Qualitative information was also used to support the interpretation of the findings. The results show that religiosity (t = 2.883; p = 0.008), access to capital (t = 2.226; p = 0.035), and entrepreneurial knowledge (t = 2.457; p = 0.021) each have a positive and significant effect on financial performance. Simultaneously, these variables also have a significant effect (F = 30.303; p = 0.000). This indicates that improvements in religiosity, access to capital, and entrepreneurial knowledge enhance the financial performance of street vendors. This study provides implications for policies aimed at empowering street vendors through strengthening religious values, improving financial access, and enhancing entrepreneurial capacity. However, the study is limited to a single location. This study contributes by integrating religiosity with economic factors in explaining the financial performance of street vendors within a mosque-based economic environment.